2008
DOI: 10.3378/1534-6617-80.3.271
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sociocultural Cleavage on Genetic Differentiation: A Study from North India

Abstract: Indian populations possess an exclusive genetic profile primarily due to the many migratory events, which caused an extensive range of genetic diversity, and also due to stringent and austere sociocultural barriers that structure these populations into different endogamous groups. In the present study we attempt to explore the genetic relationships between various endogamous North Indian populations and to determine the effect of stringent social regulations on their gene pool. Twenty STR markers were genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Studies using microsatellites highlight that genetic variation is geographically and socially This study along with other studies (Kashyap et al 2004;Khan et al 2008;Krithika et al 2009) confirmed that microsatellite genetic variation in Indian populations is structured on geographical, linguistic and caste hierarchy basis. Overall, these studies strongly show that microsatellite loci are polymorphic in Indian populations and there is no significant deficiency in heterozygosity levels as one would expect if the population was endogamous.…”
Section: Repeat Length Polymorphismssupporting
confidence: 79%
See 1 more Smart Citation
“…Studies using microsatellites highlight that genetic variation is geographically and socially This study along with other studies (Kashyap et al 2004;Khan et al 2008;Krithika et al 2009) confirmed that microsatellite genetic variation in Indian populations is structured on geographical, linguistic and caste hierarchy basis. Overall, these studies strongly show that microsatellite loci are polymorphic in Indian populations and there is no significant deficiency in heterozygosity levels as one would expect if the population was endogamous.…”
Section: Repeat Length Polymorphismssupporting
confidence: 79%
“…Both minisatellites and microsatellites are highly variable, polymorphic, co-dominant and heterozygous and thus are excellent tools for genetic individualization and population genetic studies (Papiha et al 1996a;Das et al 2002;Mastana and Singh, 2002;Das and Mastana, 2003;Ranjan et al 2003;Agrawal et al 2003;Sachdeva et al 2004;Kashyap et al 2004Kashyap et al , 2006Mastana et al 2007;Khan et al 2008). Chakraborty (1990) suggested that even a single minisatellite locus could provide information concerning sub-structuring within a population with a statistical power greater than several classical genetic markers studied simultaneously.…”
Section: Repeat Length Polymorphismsmentioning
confidence: 99%